Measuring a cash waqf giving behavior among Muslim donor in Malaysia: a theory of planned behavior approach using structural equation modeling - Osman, Amirul faiz; Mohammed, Mustafa Omar (aculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM), 2017)
This study investigated cash waqf giving behavior among Muslim donors based on the Theory of Planned Behavior. A survey was conducted on 370 Muslim donors working in government and private agencies/institutions located in Selangor Darul Ehsan, Malaysia. The data was analyzed using structural equation modeling (sem). The results indicate that attitude subjective norm, perceived behavioral control and intention are instrumental in determining cash waqf giving behavior among the sampled Muslims donors. Insight from this research are of particular importance to mutawallis in understanding cash waqf giving behavior among Muslim donors and, hence, helping them to enhance their fundraising strategies and marketing plans. Suggestion for future research are provided accordingly.